P2X4 signalling contributes to hyperactivity but not pain sensitization comorbidity in a mouse model of attention deficit/hyperactivity disorder - Bou Sader Nehme, Sarah; Sanchez-Sarasua, Sandra; Adel, Ramy; Tuifua, Marie; Ali, Awatef; Essawy, Amina E.; Abdel Salam, Sherine; Hleihel, Walid; Boué-Grabot, Eric; Landry, Marc (Frontiers in Pharmacology, 2024)
Attention deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder characterized by hyperactivity, inattention, and impulsivity that often persist until adulthood. Frequent comorbid disorders accompany ADHD and two-thirds of children diagnosed with ADHD also suffer from behavioural disorders and from alteration of sensory processing. We recently characterized the comorbidity between ADHD-like symptoms and pain sensitisation in a pharmacological mouse model of ADHD, and we demonstrated the implication of the anterior cingulate cortex and posterior insula. However, few studies have explored the causal mechanisms underlying the interactions between ADHD and pain. The implication of inflammatory mechanisms has been suggested but the signalling pathways involved have not been explored. We investigated the roles of purinergic signalling, at the crossroad of pain and neuroinflammatory pathways, by using a transgenic mouse line that carries a total deletion of the P2X4 receptor. We demonstrated that P2X4 deletion prevents hyperactivity in the mouse model of ADHD. In contrast, the absence of P2X4 lowered thermal pain thresholds in sham conditions and did not affect pain sensitization in ADHD-like conditions. We further analysed microglia reactivity and the expression of inflammatory markers in wild type and P2X4KO mice. Our results revealed that P2X4 deletion limits microglia reactivity but at the same time exerts pro-inflammatory effects in the anterior cingulate cortex and posterior insula. This dual role of P2X4 could be responsible for the differential effects noted on ADHD-like symptoms and pain sensitization and calls for further studies to investigate the therapeutic benefit of targeting the P2X4 receptor in ADHD patients.